KRITIK ATAS KRITIK IGNAZ GOLDZIHER TENTANG QIRĀ’ĀT - Ecky Syahrullah (AL ITQAN: Jurnal Studi Al-Qur'an, 2017)
Goldziher went to great length to impose the Qur'an as scripture by critisizing the Qirā'āt aspect. He argued that the existence of Qirā'āt was an evidence of inconsistency of the Qur'an in its reading variants. Goldziher also revealed that Muslims previously tried to equate the Qirā'āt, but this was not realized because it was hampered by the lack of punctuation system at that time. This article describes and analyzes some of the scholars' criticisms which has criticized Goldziher's opinion. From the analysis, it is found that Goldziher's argument is not supported by strong evidence and data, and tends to ignore historical data.